PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS LAYANAN HER REGISTRASI IGRACIAS TERHADAP KEPUASAN PENGGUNA - Viliane Puspa Negara; Dudi Pratomo (JAF (Journal of Accounting and Finance), 2019)
This research was carried out by using the model's success Information System which has been designed by DeLone and McLean (2003) by taking several required dimensions or variables. The purpose of this study was to examine the influence of information quality, system quality, service quality Her Registration process to the satisfaction of a user (A Case Study of the iGracias application Telkom University). The sample used in this study were the students of Telkom University class of 2013, which at the time of the school year 2016/2017 be final year students so that more process Her Registration compared to other forces. The sampling technique using probability sampling, with probability sampling technique used is Proportionate stratified random sampling, so that the sample in this study were 371 respondents. The study proves that the information quality, system quality, and service quality significantly influence to user satisfaction simultaneously, as well as proving that the information quality, system quality, and service quality have a positive influence and significant to user satisfaction